Strategi Guru Pendidikan Agama Kristen Dalam Mengendalikan Perilaku Perundungan di SMK N PP Kalasey - tires, maria gabriela; Selanno, Semuel; Ruindungan, Max (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aim to analyze and describe the strategies of Christian religious edication teachers in controlling bullying behavior at SMK N PP Kalaset, Minahasa Regency. This research uses a qualitative research method with a phenomenological approach. Observations, interviews, an literature studies are the researchers way of collecting data and finding information that to control bullying behavior, Christian religious education teachers are also involved in change agent groups or anti-bullting messages using appropriate learning strategies, and taking teacher approaches to students to better control students. In and knowing the most appropriate strategy to apply. While in previous research on bullying was always linked to the strategies of guidance an counseling teachers, this time the research describes a strategy that focuses on Christian religious education teachers in controlling bullying behavior at SMK N PP Kalasey, Minahasa Regency.